Manajemen Logistik Obat di Instalasi Farmasi pada Dinas Kesehatan Kabupaten Donggala - Azwar Azwar; Mustainah Mustainah; Intam Kurnia (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
This study aims to determine and analyze Management Medication Logistics at the Pharmacy Installation of the Donggala District Health Office. The theory used in this study is Siagian's theory which states that management is an activity of planning, organizing, directing and supervising carried out by each organization coordinating various data sources owned to achieve the goals set effectively and efficiently. This research method uses qualitative research that produces descriptive data through in-depth interviews in the form of written or oral statements from people and their actions that can be observed. The location of this research is at the Donggala District Health Office. The selection of informants was 3 people using the purposive method. Data collection was carried out by interview, observation, and documentation. Based on the results of the study, it was carried out according to the management process starting from planning, organizing, directing and supervising. Planning in terms of procurement, storage and distribution of drugs that have been carried out has not gone well. Procurement of drugs in shipping takes 2-3 weeks because the expedition route from outside Palu City, so there is a shortage of drugs. Drug storage is not optimal with a warehouse space that is not large enough. Drug distribution is not optimal with empty drug stocks. Organization has been done effectively with human resources as expected. Direction is carried out by the head of the pharmacy section who coordinates with the health resources sector in providing direction to employees to work well. In terms of supervision, internal meetings and quarterly meetings are held in coordination with the health resources sector in reporting performance, achievements and obstacles that occur in the field.